Three Types of Coexistence of Pagan and Christian Elements in the Late Roman Intellectuals’ Mentality - Litovchenko, Elena V.; Shilina, Sof’ya V.; Sapenko, Viktoriya Yu.; Dudka, Anna I.; Sinitsa, Marina M. (Journal of History Culture and Art Research, 2018)
The paper considers three types of coexistence of pagan and Christian elements in the consciousness of Late antique intellectuals who were Latin writers in the period from of the 4th to 6th centuries, representatives of the upper stratum, Christians such as Ausonius, Paulinus of Nola, Sidonius Apollinaris, and others. The authors come to the conclusion that the attitude to the pagan heritage combined in the minds of Late Latin intellectuals with Christian ideas in three versions: passive-eclectic, contrast-nihilistic and respectful-condescending, which was conditioned both by life circumstances and chronologically.